Implementation of the German Prevention Act: Municipal Public Health Units as a Bottleneck?. (30th September 2020) - Arnold, L; Starke, D; Szagun, B
Abstract: Background: The German Prevention Act (PrävG) came into force in 2015. As a federal law, it remains vague with regard to municipal structure. The municipalities, as those public health units that have direct access to the living environment, play a central role in the implementation of health promotion and prevention. The evaluation by the National Prevention Conference in 2019 showed that the involvement of the municipal public health services (ÖGD) has not yet been sufficiently achieved. A major problem is the heterogeneity of ÖGD units in Germany's federal structure, about which little information is available. Methods: In order to fully capture this heterogeneity for the first time, a systematic online screening was carried out. For this purpose, the websites of all 358 ÖGD units were screened independently of two researchers according to structural conditions. Results: 70% of all municipal ÖGD units are located at district level, 18% at city district level and 12% cumulatively. Population varies from 35, 000 to about 1.5 million inhabitants. The allocation of the ÖGD units to youth service planning and social welfare varies in the federal states from 18.7% to 94.4%, within regulatory agency and veterinary office from 27.8% to 79.2%. Conclusions: The heterogeneity makes the establishment of municipal standards difficult. Due to the diverse administrative allocation, different levels of policy-making must be considered on the way to health in all policies. The political classification reflects in roughly equal parts an ÖGD orientation towards health protection or social determinants of health, as recommended for the PrävG. A one-sided orientation towards health protection was shown by the temporary suspension of the use of financial resources for prevention in the course of the 2nd pandemic law to combat the COVID-19 pandemic. For the announced reform of the German ÖGD it is necessary to homogenize essential structural characteristics and to prevent a one-sided orientation. Key messages: The heterogeneity of municipal health services makes it difficult to implement the German Prevention Act. In the course of the upcoming ÖGD reform, essential structural characteristics should be homogenized and a one-sided orientation of the municipal ÖGD units towards health protection should be avoided.